Molecular and cellular mechanisms of neuronal plasticity in normal aging and Alzheimer's disease - Coleman, Paul D.; Higgins, Gerald A.; Phelps, Creighton H. (Progress in brain research, 1990)
Neuroscientists and researchers in Alzheimer's disease will find this book essential reading.